Effectiveness Of PPPK Orientation Program In Improving PPPK Performance In Wonosobo District - Indah Sri Lestari; Andriyastuti Suratman (Cita konsultindo, 2025)
PPPK orientation in the State Administration Agency (LAN) Regulation Number 15 of 2020 and LAN Decree Number 289/PDP/K.1/2022 is an activity that aims to provide an understanding and introduction to the duties and functions of ASN, values and ethics, and attitudes to defend the country. The Wonosobo Regency Government through the BKD has implemented a PPPK orientation attended by 318 participants consisting of 293 PPPK formations in 2023, 14 PPPK formations in 2022, and 11 participants in the 2022 formation optimization path. This study uses a descriptive qualitative approach methodology, involving 2 people in charge of PPPK orientation activities, and 1 PPPK orientation participant. Through this study, the author formulates the main problem, namely